“Hamro Jhora, Hamro Pani” (Our Spring, Our Water): Water and the Politics of Appropriation of ‘Commons’ in Darjeeling Town, India - Chakraborty, Anup Shekhar (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
Based on the study of Darjeeling Municipality, the paper engages with issues pertaining to understanding the matrixes of power relations involved in the supply of water in Darjeeling town in India. The discussions in the paper focuses on urbanization, the shrinking water resources, and increased demand for water on the one hand; and the role of local administration, the emergence of the water mafia, and the ‘Samaj’ (society) all contributing to a skewed and inequitable distribution of water and the assumption of proprietorship or the appropriation of water commons, culminating in the accentuation of water-rights deprivation in Darjeeling Municipal Area. HYDRO Nepal Journal Journal of Water Energy and Environment Issue No: 22 Page: 16-24 Uploaded date: January 14, 2018